Social and cultural dimensions of "medically assisted procreation". - Belardinelli, Sergio (Medicina e Morale, 2004)
From the recent law on the "medically assisted procreation", approved by Italian Parlament, the author makes some considerations that can be synthesized in two fundamental points. First, the assertion that the procreation has a social dimension, that is to recognize that it is necessary to rediscover in the procreation more than a private affair, a strong relational meaning (parents-children relationship; familysociety relationship). The second point argued by the author is the idea that the safeguard of the natural conditions of the procreation has a decisive importance for the human freedom.